La mejora de las condiciones de trabajo sobre plataformas en la unión europea consideraciones a la gestión algorítmica (salud y prevención) = Improving working conditions on platforms in the European Union : considerations for algorithmic management (health and prevention) - Kahale Carrillo, Djamil Tony (2023)
The European Commission proposes the Proposal for a Directive of the European Parliament and of the Council on improving working conditions on platforms. The future legislation aims to ensure that those working on digital platforms can enjoy the employment rights and social benefits to which all workers are entitled. This study analyses the Proposal for a Directive which aims to provide greater legal certainty by allowing workers to see their labour rights consolidated throughout the European Union; in particular, algorithmic management in which health and prevention must be taken into account.
La Comisión Europeapropone la Propuesta deDirectiva del Parlamento Europeo ydel Consejorelativa a la mejora de las condiciones de trabajo sobre plataformas. La futura normativa pretende garantizara aquellaspersonas que trabajen a través de plataformas digitalesque puedan disfrutar de los derechos laborales y las prestaciones sociales a los que tienen derechotodos los trabajadores. Este estudio analiza aquella Propuesta de Directiva en el que pretende proporcionar una mayor seguridad jurídica,al permitir que aquellos trabajadores puedan ver consolidados sus derechos laborales en toda la Unión Europea; de manera especial, a la gestión algorítmica en el que hay que tener consideración a la salud y prevención.
Keywords: Directive; European Union; digital platforms; Workers; plataformas digitales; trabajadores; Directiva; Unión Europea